Interrelationship between muscle fitness in childhood and bone mineral density in adulthood: mediation analysis of muscle fitness in adulthood - Barbosa, Cynthia Correa Lopes; da Costa, Julio Cesar; Romanzini, Catiana Leila Possamai; Batista, Mariana Biagi; Blasquez-Shigaki, Gabriela; Fernandes, Rômulo Araújo [UNESP]; Martinho, Diogo V.; Oliveira, Tomás; Ribeiro, Luís P.; Coelho-e-Silva, Manuel João; Ronque, Enio Ricardo Vaz (Springer Nature, 2023)
Background: This study was aimed to examine the relationship between muscular fitness indicators in childhood and areal bone mineral density (aBMD) in adulthood and to verify whether the relationship is mediated by performance on muscular fitness indicators in adulthood. Methods: A sample of 138 healthy adults (69 males; 22.3 years) were followed after a previous assessment at the age of 7–10 years. Stature, body mass and muscular fitness indicators (handgrip strength, standing long jump and sit-ups tests) were assessed in childhood and adulthood. Additionally, total body, upper limbs, lower limbs, right femoral neck and lumbar spine aBMD was assessed in adulthood using dual X-ray absorptiometry. Analysis included descriptive statistics; t-test or Mann-Whitney U-test for comparison between males and females, multiple linear regression for the prediction aBMD from muscular fitness indicators in childhood, mediation analysis of the respective muscular fitness indicators in adulthood and the relationship between muscular fitness indicators in childhood and aBMD. Results: Males were stronger compared to females regarding muscular fitness indicators in childhood and adulthood, and presented higher mean values for aBMD in adulthood, except for lumbar spine (p < 0.05). Regression analysis revealed that some muscular fitness indicators in childhood showed significant positive relationship with bone health indicators in adulthood, such as: handgrip strength and total body aBMD (β = 0.005; R2 = 0.35; p = 0.040) and upper limbs aBMD (β = 0.005; R2 = 0.55; p = 0.019); and sit-ups test was a significant predictors of lumbar spine BMD (β = 0.003; R2 = 0.06; p = 0.039). Mediation analysis pointed out the following: adulthood handgrip strength mediated relationships between childhood handgrip strength and total aBMD (indirect effect (IE) = 0.0025; 95%CI = 0.0005–0.0048), and upper limbs aBMD (IE = 0.0040; 95%CI = 0.0017–0.0069). Conclusions: Muscular fitness indicators in childhood showed significant relationship with bone health indicators in adulthood and the sit-ups test in childhood had direct effect on lumbar spine aBMD in adulthood. Adulthood handgrip strength mediated the relationship between childhood handgrip strength and total body and upper limb aBMD, pointing out that muscular fitness in childhood may be a aBMD determinant in adulthood, especially when higher muscle fitness performance is maintained in adulthood.
Keywords: Bone health; Growth; Muscle strength; Physical fitness